The Formation of the Pedagogue and Environmental Education (Global Journal of Human-Social Science, 2013)
It's the Greek scene is born early indications of Education through Plato, considered the first teacher for believing in the formation of wise guys, always instigating the unrest of knowing and valuing the human. We realized how old is thinking about education and pedagogy won numerous contributions to the present day. New concepts were incorporated into the ways of teaching. The ways to achieve the human faculties are studied to this day.